Multidimensional Auctions for Public Energy Efficiency Projects : Evidence from the Japanese ESCO Market - Iimi, Atsushi (World Bank, Washington, DC, 2013)
Competitive bidding is an important policy tool to procure goods and services from the market at the lowest possible cost. Under traditional public procurement systems, however, it may be difficult to purchase highly customized objects, such as energy efficiency services. This is because not only prices but also other nonmonetary aspects need to be taken into account. Multidimensional auctions are often used to evaluate multidimensional bids. This paper examines the bidding strategy in multidimensional auctions, using data from public energy service company projects in Japan. It shows that multidimensional auctions work well, as theory predicts. The competition effect is significant. In addition, strategic information disclosure, including walk-through and preannouncement of reserve prices, can also promote energy savings and investment. Risk sharing arrangements are critical in the energy service company market. In particular, the public sector should take regulatory risk.